On the Nomenclature of Common Thorny Bamboo of India - Sharma, M. L.; Singh, Arminder (Indian Forester, 1994)
The genus Bambusa Schreber is based on the type Bambos arundinacea Retzius. McClure (1946), on the basis of Retzius description and other evidence concluded that the Retzius specimen resembled Bambusa vulgaris Schrader ex Wendland and not B. arundinacea Willd., the thorny bamboo. McClure, therefore, chose the illustration of 'Illy' in Rortus indicus malnbaricus of Rheede as the type of thorny bamboo and suggested the use of the combination Bambusa bumbos (Linn.) Voss. This combination has been followed by several recent authors. Holttum, (l956b) examined the type sheet of Bambos arundinacea and concluded that it carried two elements mounted on the sheet. He chose the element on the right side of the sheet to represent the thorny bamboo of India and the type of species ofBambusa. Later, McClure (1957) also agreed with Holttum's views. Thus the correct name for the thorny bamboo of India is Bambusa arundinarea (Retz.) Willd. and not Bambusa bambos (Linn.) Voss